PERSEPSI MAHASISWA TEKNOLOGI PENDIDIKAN TERHADAP KESIAPAN KERJA MAHASISWA SETELAH MENGIKUTI PROGRAM MSIB - Ambarwati Ambarwati; Azmi Azkiyati; Linda Setiawati (EDUTECH, 2023)
Abstract. The development of technology in this era is growing rapidly. This has had a major impact on several sectors in Indonesia, be it the education, economic, political, health, social or cultural sectors. This development makes the process of finding information easier, one of which is in the education sector. This technological development has made the education sector more diverse in terms of innovation, this can be seen from the learning process which is increasingly innovative and relevant to its development. In addition, the Minister of Education and Culture Nadiem Makariem made a new breakthrough in terms of education, one of which was Merdeka Belajar-Kampus Merdeka. Merdeka Belajar-Kampus Merdeka policy is a form of learning in higher education that is autonomous and flexible so that it can create an innovative learning culture that is not restrictive and in accordance with the needs of students. The program was created with the aim of improving students' soft skills hard skills in developing their skills. Therefore this program needs to be implemented, then the authors conduct research in terms of student perceptions, especially educational technology study programs, on their work readiness after participating in the program that was created, namely the MSIB program. From this collection of perceptions, it is hoped that the MSIB program will be able to gain new perspectives and feedback related to the programs that have been implemented. The authors collect data using a quantitative descriptive method with a questionnaire containing a number of statements with an assessment using a dichotomous scale. The questionnaire is divided into 2 parts, namely personal data and statements related to MSIB. There were 13 statements related to MSIB given to respondents relating to the level of knowledge, interest, and respondents' perceptions of the MSIB program.Keywords: Perception, Program, Work, Policy